2021
DOI: 10.48550/arxiv.2104.03029
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ramified class field theory and duality over finite fields

Abstract: We prove a duality theorem for the p-adic étale motivic cohomology of a variety U which is the complement of a divisor on a smooth projective variety over F p . This extends the duality theorems of Milne and Jannsen-Saito-Zhao. The duality introduces a filtration on H 1 ét (U, Q Z). We identify this filtration to the classically known Matsuda filtration when the reduced part of the divisor is smooth. We prove a reciprocity theorem for the idele class groups with modulus introduced by Kerz-Zhao and Rülling-Sait… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Theorem 1.1 [Theorem 7.3] Let k be a field satisfying resolution of singularities and weak factorisation in the sense of Def.A.4, e.g., a field of characteristic zero, Cor.A.6, Thm.A. 7.…”
Section: -Invariant Cohomology Theory H Imentioning
confidence: 99%
See 1 more Smart Citation
“…Theorem 1.1 [Theorem 7.3] Let k be a field satisfying resolution of singularities and weak factorisation in the sense of Def.A.4, e.g., a field of characteristic zero, Cor.A.6, Thm.A. 7.…”
Section: -Invariant Cohomology Theory H Imentioning
confidence: 99%
“…where O(X ∞ −|X ∞ |) is the line bundle associated to the divisor X ∞ −|X ∞ |. 2 Krishna and Gupta have shown that Chow groups with modulus CH 0 (X ) cannot be isomorphic to the cohomology theory hom MDM eff k (M(X ), Z(d)[2d]) with d = dim X as they do not satisfy Nisnevich descent, [7,Thm. 1.5].…”
Section: -Invariant Cohomology Theory H Imentioning
confidence: 99%
“…1.4], we obtain the following reciprocity theorem for Russell's relative Chow group. Let π abk 1 (X, D) be the log version (see [21,Defn. 9.6] or [4,Defn.…”
Section: Class Field Theory Ofmentioning
confidence: 99%
“…1.4], we obtain the following reciprocity theorem for Russell's relative Chow group. Let π abk 1 (X, D) be the log version (see [24,Defn. 9.6] or [4,Defn.…”
Section: Introductionmentioning
confidence: 99%